Analysis of BRCA1 and BRCA2 mRNA levels in different cell types derived from BRCA germline mutation carriers - Gordon, Pedro Galhardo Bak (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021